The Institutions of Programmatic Action Policy Programs in French and German Health Policy - Hornung, Johanna (International Series on Public Policy, 2022)
This open access book is the first monograph to systematically apply the Programmatic Action Framework (PAF) in a comparative analysis of public policy in two institutionally different countries. The PAF seeks to explain long-term policy change by examining the shared biographies of policy actors who, to foster their careers, coalesce around policy programs which they promote throughout the policy process. Comparing health policy-making in France and Germany between 1990 and 2020, the book sheds light on the institutional settings that are necessary for programmatic action to occur. It will appeal to scholars and students of public policy, public administration, and health policy.